Massive In vitro Propagation from Cultured Nodal Segment of Three Citrus species - Vibhute, Megha; Tripathi, M. K.; Tiwari, R.; Tiwari, Sushma; Tripathi, Niraj; Sharma, Mohini; Tomar, Yashi Singh; Tiwari, Sharad (Research Aspects in Biological Science Vol. 6, 2022)
Nodal sections excised from in vitro grown saplings of three citrus species viz., Citrus aurantiafolia, Citrus reticulata and Citrus sinensis were inoculated on diverse modifications of basal MS medium for manifold shootlet production. In vitro morphogenesis followed by plant regeneration speckled significantly among species and culture medium fortification. In this investigation, shootlets were developed directly via auxiliary bud proliferation along with from callus tissue. Culture medium MS5N.5B/MS5N.Kn (MS + 5.0 mgl-1 NAA + 0.5 mgl-1BA/Kn) convinced callusing in higher rates. Nutrient medium MS.1Td.5N/MS.5B.5N (MS + 0.1 mgl-1 TDZ/0.5 BA + 0.5 mgl-1 NAA) boosted plantlet multiplying competence. Whereas, plantlets per explant in higher frequencies (s) of bigger length were recognized on nutrient medium MS.1Td or MS.2Td (MS + 0.1/0.2 mgl-1 TDZ). In respect to in vitro rooting, root initiating efficacy in higher frequencies was verified on medium MS.5IB (MS + 0.5 mgl-1 IBA), while roots in greater numbers were documented on rooting medium MS2IB.5Kn (MS + 2.0 mg l-1 IBA + 0.5 mg l-1 Kn), whereas nutrient medium MS.5IB.5B (MS + 0.5 mg l-1 IBA + 0. 5 mg l-1 BAP) improved mean root length. In respect to interspecific in vitro response, usually, Acid lime tracked by Mandarin and Sweet orange performed authoritatively for the almost culture stages. The in vitro developed shootlets were efficaciously adapted and shifted under field conditions.